MRI of the Wrist Ligaments. Issue 5 (October 2020) - Leake, Richard L.; Mills, Megan K.; Allen, Hailey; Crawford, Amanda M.; Kobes, Patrick H.; Soltanolkotabi, Maryam
Abstract : Abstract: Technological advances in magnetic resonance imaging (MRI) have improved radiologists' ability to evaluate wrist ligaments. MRI interpretation often guides clinical management. This article aims to review the normal and pathologic appearance of intrinsic and extrinsic wrist ligaments with a focus on MRI. Variant anatomy, imaging pearls, and clinical significance are also discussed. Special attention is paid to key wrist ligaments that play a role in carpal stability.